Respuestas

  • Usuario de Brainly
2013-08-29T00:36:59+02:00
opcion a

(2x)^2 - 5x------ para\ x= \frac{1}{2} \\ \\4x^2-5x\\ \\4( \frac{1}{2})^2-5( \frac{1}{2})\\ \\4( \frac{1}{4})- \frac{5}{2}\\ \\4-    \frac{5}{2}=\frac{8-5}{2}=\frac{3}{2}

por si te referias a esta otra expresion

2x^2-5x----para\ x= \frac{1}{2}\\ \\2(\frac{1}{2})^2-5(\frac{1}{2})\\ \\2(\frac{1}{4})-\\\frac{5}{2}\\ \\\frac{1}{2}-\frac{5}{2}=\frac{-4}{2}=-2

opcion b

 -(x+y-5)^2....para\ x=-1\ ;\ y=6\\ \\-(x+y-5)\cdot(x+y-5)\\ \\-[x^2+xy-5x+xy+y^2-5y-5x-5y+25]\\ \\-[x^2+y^2+2xy-10x-10y+25]\\ \\-x^2-y^2-2xy+10x+10y-25\\ \\-(-1)^2-(6)^2-2\cdot(-1)\cdot6+10\cdot(-1)+10\cdot6-25\\ \\-1-36+12-10+60-25

-1-36+12-10+60-25\\-37+62-25\\72-72=0\ La\ respuesta\ es\ igual\ a\ cero

Solución: 0